Landfill Leachate Degradation by TiO2-Immobilized White Cement - Ni Wayan Yuningrat; I Putu Parwata; Putu Frisca Dora Jastrissia; Made Vivi Oviantari; I Wayan Mudianta (Molekul, 2018)
This report presented the characterisation of white cement and TiO2-immobilised white cement prior and after photodegradation treatment. The study was also aimed at measuring the effectiveness of catalyst that was used during the photodegradation at various different reaction times. The characteristic of the white cement was evaluated by XRD, meanwhile the effectiveness of the catalyst was inferred from COD values. The results indicated that the white cement formed crystals with highest peak at 2ϴ 29.7990° and crystal size of 0.63140 nm. In addition, the highest peak of the TiO2-immobilized white cement before and after photodegradation was 2ϴ 29.4634° (crystal size 0.79209 nm) and 29.4735° (crystal size 0.64061 nm) respectively. Moreover, dissolved organic matter in landfill leachate reduced during the seven-hour photodegradation experiment as indicated by the decrease of 71.43% of the COD values.